Tetrazine derived mononuclear Ru-II(acac)(2)(L)(1), [Ru-II(bpy)(2)(L)](ClO4)(2)(2) and [Ru-II(bpy)(L)(2)](ClO4)(2)(3) (L=3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate, bpy=2,2 '-bipyridine): syntheses, structures, spectra - Nayak, A.; Patra, S.; Sarkar, B.; Ghumaan, Sandeep; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Polyhedron, 2005)
Mononuclear ruthenium complexes of tetrazine derived L, Ru-II(acac)(2)(L) (1), [Ru-II(bpy)(2)(L)](ClO4)(2) (2) and [Ru-II(bpy)(L)(2)](ClO4)2 (3) (L = 3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate and bpy = 2,2'-bipyridine) were prepared. The free L exists as a dimeric entity in the solid state via hydrogen bonding interactions involving L and water molecules present in the crystal lattice. 1 exhibits unusually strong bonds from Ru-II to coordinating pyrazolyl-N (2.040(2) Angstrom) and especially to tetrazine-N (1.913(2) Angstrom). The Ru-III/Ru-II couples of 1-3 appeared at 0.28, 1.34 and 1.50 V versus SCE, respectively. The tetrazine and bpy-based reductions were observed at -1.33 (1); -0.55 and -1.55/-1.75/-1.98 (2); -0.47/-0.78 and -1.80/-2.02 V (3), respectively. 1, 2 and 3 displayed two MLCT bands each, corresponding to dpi(Ru-II) --> pi* (L, tetrazine) and dpi(Ru-II) --> pi* (acac or bpy or L) transitions. 1(+) and 2(+) showed rhombic EPR spectra at 110 and 4 K, respectively and 1(-), 2(-) and 3(-) exhibited multiple line EPR spectra at 300 K. 1-3 exhibited moderately strong emission spectra in EtOH-MeOH glass at 77 K. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Electrochemistry; redox; ruthenium-tetrazine; spectra; structure; synthesis

Influence of organic modification on mechanical properties of melt processed intercalated poly(methyl methacrylate)-organoclay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Applied Polymer Science, 2007)
The influence of organic modifiers on intercalation extent, structure, thermal and mechanical properties of poly(methyl methacrylate) (PMMA)-clay nanocomposites were studied. Two different organic modifiers with varying hydrophobicity (single tallow versus ditallow) were investigated. The nanocomposites were prepared from melt processing method and characterized using wide angle X-ray diffraction, transmission electron microscopy, thermogravimetric analysis, differential scanning calorimetry (DSC), and tensile tests. Mechanical properties such as tensile modulus (E), break stress (sigma(brk)), and 0% break strain (epsilon(brk)) were determined for nanocomposites at various clay loadings. Extent of PMMA intercalation is sufficient and in the range 9-15 angstrom depending on organoclay and filler loading. Overall thermal stability of nanocomposites increases by 16-30 degrees C. The enhancement in T-g of nanocomposite is merely by 2-4 degrees C. With increase in clay loading, tensile modulus increases linearly while % break strain decreases. Break stress is found to increase till 4 wt % and further decreases at higher clay loadings. The overall improvement in thermal and mechanical properties was higher for the organoclay containing organic modifier with lower hydrophobicity and single tallow amine chemical structure. (c) 2007 Wiley Periodicals, Inc.
Keywords: mechanical properties; Nanocomposites; organoclay; structure; Thermal properties

Ab initio calculations of the geometry and polarizabilities of bisphenyls having aliphatic substituents - Sulatha, M. S.; Natarajan, U. (International Journal of Quantum Chemistry, 2011)
Ab initio geometry optimization and polarizability calculations of a series of bisphenyls, which are the model compounds of chemically different polycarbonates using HF/6-31G and 6-31G** basis sets are presented. Calculated absolute value of the conformationally averaged optical anisotropy (<gamma(2)>) of diphenyl propane, a model analog of bisphenol A polycarbonate, is higher than the corresponding experimental value in the dilute solution phase. The calculations have reproduced the relative trend in the optical anisotropy for the different bisphenyl model compounds in a manner similar to those using semiclassical approach, by incorporation of the condensed phase polarizabilities and quantum chemically calculated geometry structure into the valence optical scheme. Individual contributions to the gas phase polarizability and optical anisotropy of the model compounds for various dihedral conformers, because of the presence of different aliphatic chemical groups, are correctly predicted by the calculations here. (C) 2010 Wiley Periodicals, Inc. Int J Quantum Chem 111: 1092-1100, 2011</gamma(2)>
Keywords: ab initio; bisphenyl; optical anisotropy; polarizability; Polycarbonate; structure

Structure-property relationship of different types of polyester industrial yarns - Samui, Barun Kumar; Prakasan, Manikanda Priya; Ramesh, C.; Chakrabarty, Debabrata; Mukhopadhyay, R. (Journal of the Textile Institute, 2013)
Four major types of polyester industrial yarns (1000 Denier) which are used commercially were studied for their key structural parameters. An attempt has been made to establish a relationship between morphology and properties of these yarns. High tenacity (HT) polyester yarn has the highest birefringence, amorphous orientation, and long period but is relatively less crystalline. High shrinkage characteristic of HT polyester yarn can be accounted for its higher amorphous orientation. High modulus low shrinkage (HMLS) polyester yarn has higher crystallinity and crystal size compared to HT yarn. Fraction of tie molecules of these yarns has been calculated and found that low shrinkage (LS) and super low shrinkage (SLS) yarns have lesser tie molecules. These LS and SLS yarns are tailor-made to achieve lower shrinkage and at the same time maintaining a good level of tenacity. This is achieved with lower amorphous orientation in the final drawn yarn structure. Amorphous orientation was found to have stronger influence than any other structural parameter on the key yarn properties like modulus, tenacity, elongation, and shrinkage.
Keywords: modulus; orientation; polyester; shrinkage; structure

Isolation and structural characterization of exopolysaccharide from marine Bacillus sp. and its optimization by Microbioreactor - Wagh, Vasudev S.; Said, Madhukar S.; Bennale, Jagadish S.; Dastager, Syed G. (Carbohydrate Polymers, 2022)
In the present study, a cost-effective, robust Microbioreactor based production optimization of levan like exopolysaccharide from marine Bacillus sp. SGD-03 was analysed. FE-SEM analysis has showed the significant fibrillar structure of EPS. Size exclusion chromatography and other analytical data revealed that, produced EPS has a molecular weight of 1.0 x 10(4) Da and is composed of fructose monosaccharide with hydroxyl, carbonyl, and ether groups. The backbone structure of EPS has a branching pattern of beta-(2,6) linkages which confirms the similarity with available levan like polymers. The cost-effective media composition for levan production was demonstrated. The maximum yield of crude levan obtained was 123.9 g/L by response surface methodology using robust BioLector Pro Microbioreactor, and same has been validated with shake flask, 1 L and 10 L pilot-scale fermentation.
Keywords: EPS; marine; Microbioreactor; Optimization; structure